(untitled) - AMALIA JUHARA, MUTIA (LATERNE, 2013)
Prepositions in German is considered difficult to study because of changes in the follow article noun and verb that follows in German that must be fitted with an object said depan.salah suitable alternative instructional media are mockups. With mock media, students or learners can view or record the location or position of building a real place. In addition, students can touch and change the location of the building miniatures in the maket. Formulation of the problem are: 1) How to increase students’ mastery of the Preposition in German languagebefore the media using mockups?, (2) How to increase mastery of the German language after the use of prepositions maket media? The purpose of this study was to determine the students’ mastery of the preposition through use of the media mockups. Quantitative research approach. The data of this study is the result of "Pre-test and Post-test". File were analyzed by t-test formula. In testing the value of t obtained results taccount and tTable = 17.713 = 2.051. This represents a significant increase in the mastery of the Preposition in German languagestudents through the use of media mockups. Keywords: German, prepositions, mockups